(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The aim of the current research is to identify the level of availability of written expression skills included in the Arabic language curriculum document among middle school students from the teachers’ point of view. The researcher used the descriptive approach. To analyze the data and access the research results, he used the (SPSS) program. The research was conducted during the first semester of the academic year 1442/1443 AH on a random sample of Arabic language teachers in the Bisha Education Department. They reached about (213) male and female teachers. The results revealed a number of indicators: the level of availability of written expression skills among middle school students in Bisha governorate from the point of view of the sample is medium in skills of (sentence production, text production, text disposal, and writing letters), where the general mean averages, respectively, amounted to (2.14; 2.15; 2.25; 2.32). The sample recognized that the skill of filling out the form was highly available, where the mean was (2.38). The results also revealed a statistically significant difference due to the gender variable in favor of the female teachers; This indicates that female teachers showed higher estimates of what middle school students possess of written expression skills compared to male teachers. The results revealed a statistically significant difference due to the variable years of experience in favor of those who have more than (10) years of experience in all sub-writing skills and the total score. This means that those who have experience (10) years or more have shown high estimates of what middle school students possess of written expression skills compared to those who have less than (10) years of experience. In light of these results, the researcher presented a number of recommendations including the need to develop the students’ written expression skills, especially the skills that were available at a medium level.